Role of SCO-792, A Novel Enteropeptidase Inhibitor, In the Prevention of Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis - Rashid, Mohammed Yousif; Gnawali, Anupa (Digestive Disease Interventions, 2021)
Acute pancreatitis is the most common iatrogenic dilemma of endoscopic retrograde cholangiopancreatography, and it is associated with significant morbidity and mortality. Several factors have been implicated in the pathogenesis of post-endoscopic retrograde cholangiopancreatography pancreatitis, and preventive measures were practiced accordingly. This study aims to refine the potential mechanisms that trigger post-endoscopic retrograde cholangiopancreatography pancreatitis and define the role of enteropeptidase in the pathogenesis of post-endoscopic retrograde cholangiopancreatography pancreatitis. Furthermore, address the role of a new novel medication known as SCO-792, a potent enteropeptidase inhibitor, in the prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis.Post-endoscopic retrograde cholangiopancreatography pancreatitis is caused by premature activation of the pancreatic enzymes within the pancreatic parenchyma. This activation is either an autoactivation due to direct provocation of intra-acinar enzymes as a result of the procedure or due to activation by enterpeptidase, a rate-limiting enzyme. Endoscopic retrograde cholangiopancreatography interjects duodenal juice that is rich in enterokinase into the pancreatic-biliary tract, which in turn leads to intra-ductal activation of trypsinogen and subsequent enzymes. Given the vital role of enterokinase in initiating the pathogenesis of pancreatitis, enteropeptidase inhibition may prevent and reduce the severity of post-endoscopic retrograde cholangiopancreatography pancreatitis.SCO-792, a novel enteropeptidase inhibitor, is developed by SCOHIA Pharma, and pre-clinical trials confirmed its efficacy in inhibiting enteropeptidase. Studies are needed to confirm the efficacy of enteropeptidase inhibitors in preventing post-endoscopic retrograde cholangiopancreatography pancreatitis.
Keywords: pancreatitis; ERCP; post-ERCP pancreatitis; enteropeptidase; SCO-792